Dhikr as an Adaptive Spiritual Strategy: Exploring the Healing Mechanism for Anxiety from The Islamic Perspective - Nurul Aisatul Masita; Cholil (Faculty Ushuluddin, Adab and Dakwah UIN Palangka Raya, 2025)
This study aims to explore in-depth individual experiences utilizing the practice of dhikr (remembrance of God) as a spiritual and holistic method for managing anxiety. Using a qualitative approach and a phenomenological design, this research focuses on the subjective meanings and cognitive, emotional, and physical changes experienced by subjects in response to regular dhikr practice. The study involved individuals aged 18 to 50 who experienced mild to moderate anxiety and had been practicing dhikr regularly for at least six months. Data were collected through in-depth interviews, participant observation, and reflective journals. Interpretive thematic data analysis revealed that dhikr functions as a spiritually integrated coping mechanism and results in a transformation of the experience of anxiety across three domains. Cognitively, dhikr is experienced as a